PENDAMPINGAN DALAM KEGIATAN MUHAFADZAH DAN MUSYAWARAH KITAB KUNING BAGI SANTRI PUTRI DI PONDOK PESANTREN SALAFIYAH SYAFI’IYAH SUKOREJO SITUBONDO - Khulusinniyah Khulusinniyah; Ahmadi Ahmadi (LP2M Universitas Ibrahimy, 2019)
Abstract: Muhafadzah and discussion Book a mastery program in the yellow book Shafi'ites Salafi pesantrenSukorejo Situbondo. Assistance to the activities and deliberations muhafadzah the book is done every Fridaywith the approach Inquiry discovery learning, the approach requires students to actively activism and find theirown knowledge, while the mentors as facilitators and alternative discussion partner for the students. Theactivity was carried out with a nice atmosphere so as to create an effective learning, the achievement oftargets SKL boarding school in the mastery of the yellow book. Pupils are stimulated to think creatively andfind their own answers from the book of specified materials companion / mentor meetings. Supervisor positionitself as a partner to learn the students and create an atmosphere of democratic deliberation so that studentscan successfully build knowledge